Kajian Linguistik Terhadap Lafaz Khair, Thoyyib, dan Hasan dalam Al-Qur’an Perspektif Imam Al-Baidhowi Tafsir Tanwir At-Tanzil Wa Asrar Fi Ta’wil - Prasetyo, Azhar Majid; Zuhri, Ahmad (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
The Qur’an, as the word of Allah, holds a central position in Islamic teachings and functions as a timeless source of law. A crucial aspect of interpretation lies in the linguistic analysis of words that may appear similar in translation but differ in semantic meaning, such as khair, ṭayyib, and ḥasan. This study aims to examine the semantic differences among these three terms based on the Tafsīr Tanwīr at-Tanzīl by Imam al-Bayḍāwī. Employing a qualitative approach with semantic analysis as its method, the study also incorporates data triangulation and methodological techniques to ensure the validity of its findings. The results indicate that al-Bayḍāwī provides a rich and contextual interpretation: khair is defined as goodness encompassing both material and spiritual dimensions; ṭayyib is understood as something good both outwardly and inwardly, aligning with the principles of lawfulness and blessing; while ḥasan refers to a form of goodness that includes aesthetic, moral, and spiritual values. These findings highlight the importance of linguistic approaches in Qur’anic interpretation and demonstrate al-Bayḍāwī’s significant contribution to the expansion of Islamic scholarship through a holistic exegetical methodology.